Evolución de los conceptos ácido-base a lo largo de la enseñanza media - Bardanca, M.; Nieto, M.; Rodríguez, Mª C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
The aim of this paper is to know the evolution of the concept of acids and bases throughout the different courses of Secondary School.